How different policy instruments affect the creation of green energy innovation: A differentiated perspective - Spyros Arvanitis; Michael Peneder; Christian Rammer; Tobias Stucki; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2016)
Based on representative firm-level survey data for the three countries Austria, Germany, and Switzerland, we investigate the effects of regulation, energy taxes, voluntary agreements, and subsidies, on the creation of green product innovations. Our data set allows us to distinguish between the supply-side effects (cost effects) and the demand-side effects of policy measures, which improves our understanding of the frequently observed positive net effect of policies. Controlling for the demand effect, taxes and regulations are negatively related with product innovations. Hence, if taxes and regulation do not trigger additional demand, they decrease the propensity to innovate. These effects are ameliorated for technologically very advanced firms and for firms with a high level of financial awareness. Subsidies and (partly) voluntary agreements are positively related with product innovations.
Keywords: O30; O34; Q55; 330; Innovation; policy; demand